"Sharia on a Plate?" A critical discourse analysis of halal food in two Norwegian newspapers. (14th September 2015) - Thomas, Paul; Selimovic, Amina
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This study aims to explore how two Norwegian national online newspapers, Dagbladet and Aftenposten, have framed halal food in the past 6 years (2008-2014), a period conflating with a rise in Muslim demographics in Norway. Design/methodology/approach – A mixed-methods approach is used. Employing among others a Hallidayan transitivity analysis and other approaches from critical discourse analysis (CDA), clausal semantic structures, collocations and nominalizations were explored with a view toward fleshing out ideological significance. Particular attention was given to the neologism – "covert-Islamization" – popularized by the populist right-wing Progress Party. Findings – The findings reveal that Dagbladet refracts halal food through a discourse of crime and other dubious frames tapping into topoi of Islamophobia. Halal is, in this manner, transformed into a synecdoche for deviance. This is contrasted with Aftenposten's more "halal-friendly" gaze which inter alia is attributed to greater access for Muslim contributors (over 40 per cent), with nearly all authorship penned in the aftermath of the Breivik massacre of July 22, 2011. Research limitations/implications – As a comparative research that explores two newspapers – albeit with substantial national circulation – there are obvious limitations. Future research could explore the contents of Verdens Gang, the biggest newspaper in Norway, and perhaps incorporate iconic semiotic content. Social implications – The prevalent media discourse on halal in Norway casts a shadow over a fundamental aspect of the identity construction of Norwegians who adhere to Islam, thus highlighting issues of belonging and citizenry in the "new" Norway. National discourses of identity and belonging impact upon the Muslim consumer's perception of self and ethnicity, and how these perceptions are negotiated in the interstices of a skewed media coverage of halal certainly serves to undermine this self-perception. Originality/value – Several recent studies have broached the subject of the manifold representations of Muslims and Islam in the media using a CDA, but there is a dearth in studies with a specific focus on halal food. This study contributes to the lacuna in the literature in an area of growing importance, not just as a socio-political and religious phenomenon, but a lucrative commercial project in a Scandinavian context.